1994
DOI: 10.1117/12.174013
|View full text |Cite
|
Sign up to set email alerts
|

<title>Video compression algorithm for dynamic angiographic images</title>

Abstract: We have developed a compression algorithm which achieves high compression ratio and excellent reconstruction quality for video rate or sub-video rate angiograms. Commercially available technology such as JPEG and MPEG do not satisfy medical requirements due to their severe block artifacts. Our new method takes advantage of the high temporal correlation of the angiographic frames using MPEG motion estimation software, but performs the error frame encoding using wavelet transfonn which is much more sensitive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The first attempts to code a sequence of medical images were to hypothesize the collection of these images in time domain and methods similar to video coders, like MPEG, were used [12]. However it has been shown that that such algorithms are not adapted to the compression of 3D CLSM images because images are obtained as optical sections at different locations along the optical axis [19] and the motion compensation techniques cannot effectively capture the pixel-intensity correlations across consecutive frames [8].…”
Section: Introductionmentioning
confidence: 99%
“…The first attempts to code a sequence of medical images were to hypothesize the collection of these images in time domain and methods similar to video coders, like MPEG, were used [12]. However it has been shown that that such algorithms are not adapted to the compression of 3D CLSM images because images are obtained as optical sections at different locations along the optical axis [19] and the motion compensation techniques cannot effectively capture the pixel-intensity correlations across consecutive frames [8].…”
Section: Introductionmentioning
confidence: 99%
“…In 3D case, many approaches, closed to the MPEG standard [18], using block matching algorithm for motion estimation has been developed [20,24] to code medical 2D sequences as numerical angiographies. Such algorithms are not adapted to the compression of real 3D medical images because of the artefacts introduced when quantizing the third dimension which are not acceptable for static data.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, using a metric sensitive to block artifacts [12], Ho et a1 concluded that for similar amounts of lossy compression in coronary and neuro angiograms the block-encoded methods introduced significantly more block artifacts. This would suggest that the motion wavelet codec would perform even better then the motion JPEG codec based on a block artifact metric.…”
Section: Discussionmentioning
confidence: 98%